2012
DOI: 10.2527/jas.2012-5263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calving distribution on beef cattle progeny performance

Abstract: Records collected between 1997 and 2010 were used to determine the effect of calving period on heifer (n = 1,019) and steer (n = 771) progeny from the Gudmundsen Sandhills Laboratory, Whitman, NE. Progeny were classified as being born in the first, second, or third 21-d period of the spring calving season within year. Heifer birth BW was lightest (P < 0.01) for heifers born in the first period. Birth to weaning ADG tended (P = 0.10) to be least for heifers born in the first calving period; however, weaning BW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 12 publications
2
37
0
6
Order By: Relevance
“…In the present study, the advantage in Julian day of calving decreased to only ~2 to 3 d in the second calving season. When Funston et al (2012) grouped heifers based on their own birth period, the advantage for Julian day of calving for the calves born in the first calving period was only 5 to 7 d. Thus, it appears that more than an advanced age at first calving is contributing to the improved fertility associated with calving early as a heifer and selecting a replacement heifer based on the date she becomes pregnant is better than selecting her based on age.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, the advantage in Julian day of calving decreased to only ~2 to 3 d in the second calving season. When Funston et al (2012) grouped heifers based on their own birth period, the advantage for Julian day of calving for the calves born in the first calving period was only 5 to 7 d. Thus, it appears that more than an advanced age at first calving is contributing to the improved fertility associated with calving early as a heifer and selecting a replacement heifer based on the date she becomes pregnant is better than selecting her based on age.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is not enough to recoup her development costs, it is better than a replacement heifer that does not produce a calf, a risk that still exists if heifers are chosen on age or BW alone. Although there appears to be inherent fertility based on calving early in the first calving season, not all of this is captured simply by selecting the oldest heifers as replacements, as suggested by Funston et al (2012). Minick Bormann and Wilson (2010) reported that age at first calving had a greater heritability than calving day (0.28 vs. 0.07), but that it was not a good indicator of inherent fertility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations